Symptomatic aberrant right subclavian artery—A case report and anesthetic implications - G J Murukendiran; Prasanta Kumar Dash; Aspari M Azeez; Nithiyanandhan Palanisamy; Shivanesan Pitchai (Annals of Cardiac Anaesthesia, 2022)
Vascular compression of the esophagus by an aberrant right subclavian artery (aRSA) leading to dysphagia is a rare occurrence. There has been a significant advancement in the diagnostic and surgical treatment modalities available for this disorder. Anesthetic management has evolved too and this case report highlights the anesthetic management of a 41-year-old woman presenting with symptoms of dysphagia because of compression of esophagus by an aRSA, who subsequently underwent re-implantation of aRSA into ascending aorta.